2007
DOI: 10.1071/en07071
|View full text |Cite
|
Sign up to set email alerts
|

Sea-salt particles and the CLAW hypothesis

Abstract: Environmental context. When proposing that dimethyl sulfide (DMS) releases from phytoplankton had a role in regulating the global climate, the potential parallel influences of sea spray aerosols on climate were largely disregarded. Over the intervening 20 years, scientific studies have clearly demonstrated a substantial role for sea spray particles in modifying cloud properties and influencing global sulfur cycling, diminishing the significance of the DMS-based CLAW mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Sea salt particles have the necessary properties to act very efficiently as CCN. [105,106] Other work confirms the role of sea salt as CCN, [107,108] with sea salt particles representing between 5 and 90% of CCN in the MBL. [109] It is now possible to directly measure the flux of sea salt from the surface of the ocean [110] and this along with laboratory studies of breaking bubbles [111] is improving the understanding of the relative contribution of sea salt to CCN number concentrations.…”
Section: Feedbacksmentioning
confidence: 56%
“…Sea salt particles have the necessary properties to act very efficiently as CCN. [105,106] Other work confirms the role of sea salt as CCN, [107,108] with sea salt particles representing between 5 and 90% of CCN in the MBL. [109] It is now possible to directly measure the flux of sea salt from the surface of the ocean [110] and this along with laboratory studies of breaking bubbles [111] is improving the understanding of the relative contribution of sea salt to CCN number concentrations.…”
Section: Feedbacksmentioning
confidence: 56%
“…Uncertainties still exist in the quantification of the influence of DMS on climate in a future climate scenario. Recent works (Yoon and Brimblecombe, 2002;Pierce and Adams, 2006;Smith, 2007) have shown that the sea salt aerosols play a role in marine CCN production. Further improvements are needeed to include sea salt in a wide range of size distribution realistically to quantify the role of DMS-sea salt interactions in global climate models.…”
Section: Discussionmentioning
confidence: 99%
“…The FN parameterization is one of the most (Fountoukis and Nenes, 2005). In addition to treating the competition among all modes, the FN parameterization can also include the presence of surfactants and slightly soluble species (Shulman et al, 1996;Laaksonen et al, 1998). The FN parameterization includes a size-dependent mass transfer coefficient for the growth of water droplets to accommodate the effect of size (and potentially organic films) on the droplet growth rate.…”
Section: Aerosol Activation Parameterizationmentioning
confidence: 99%